Decoupled State-Feedback Based Control Scheme for the Distributed Generation System. Issue 5 (16th March 2018) - Elnady, Amr; Adam, Ali
Abstract: This article presents a new development for the decoupled state-feedback control to operate the distribution generation unit (DGU) within an efficient distribution generation system (DGS). The developed decoupled state-feedback is better than the conventional voltage vector control and sliding mode control for dealing with active and reactive power. Therefore, it is embraced to form a new control scheme, which is employed to effectively decouple and precisely control the injected active and reactive power to the distribution system. A five-level diode-clamped inverter is adopted to build the DGU in order to minimize the injected harmonics, facilitate the operation of the proposed control scheme, and ease the design of its passive filter. The proposed control scheme enables the DGS to be functional in several operational modes such as grid-connected, intentional islanding, unintentional islanding, anti-islanding, and ride-through modes. The effectiveness of the proposed control scheme is proved through the simulation results for all foregoing modes. Experimental results are provided to show how the proposed concepts are practically implemented to control the voltage of the DGU so that the active power and reactive power are exchanged between the power grid and the DGS in the grid-connected mode.